The Factors that Influence Generation Z's Purchase Intention Towards Imported Secondhand Clothes In Indonesia - Dharma, I Ketut Wira (Journal Integration of Management Studies, 2023)
The development of fashion trends continues to move from time to time. In Indonesia itself, the fashion trend that is currently emerging is thrifting or buying and selling of imported secondhand clothes. Based on data from the Badan Pusat Statistik (BPS), the import value of secondhand clothing has increased significantly by 607.6% (year on year) for the January-September 2022 period. This raises a problem which is, so far, the import of secondhand clothing has cut the MSME market share in the fashion industry by 15-20%. This could happen because society, especially Generation Z, prefers to buy imported used clothes rather than buying local brand clothes, which is supported by the results of preliminary research. Therefore, the purpose of this study is to find out what factors that influence Generation Z's purchase intention towards imported secondhand clothing. Based on previous studies and the results of preliminary research, the authors used 8 factors that have an influence relationship with purchase intention, which are, frugality, eco-consciousness, need for status, need for uniqueness, fashion involvement, reference group, perceived quality, and bargain hunting. The research method used an online questionnaire survey and analyzed using descriptive text and PLS SEM with SmartPLS. A total of 356 respondents filled in the questionnaire, which is Generation Z, living in Indonesia with the requirement that they have at least bought imported used clothes at least twice in the past 3 years. The results of this study found that the need for uniqueness, fashion involvement, reference group, and perceived quality, and bargain hunting significantly influence the intention to buy imported used clothing. On the other hand, eco-consciousness and need for status indirectly affect the intention to buy imported used clothing through a mediating variable, which is bargain hunting. Frugality has a significant direct effect on the intention to buy imported used clothing and has a significant indirect effect through bargain hunting. The results of these findings provide insight to local fashion brands regarding what factors influence Generation Z's purchase intention towards imported secondhand clothes.